2018
DOI: 10.1007/s40471-018-0176-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Medication Safety Using Only Dispensing Data

Abstract: Purpose of ReviewThe purpose of this review is to provide an overview of the published studies that have been used to generate evidence on the safety of medicine use when only medication dispensing data are available.Recent FindingsMedication dispensing databases are increasingly available for research on large populations, particularly in countries that provide universal coverage for medicines. These data are often used for drug utilisation studies to identify inappropriate medicine use at the population leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…This is particularly useful with complex patients who have multiple prescribers and more than one condition requiring treatment. Medication dispensing databases are increasingly available for pharmacists on large populations, particularly in countries that provide universal coverage for medicines [28][29][30].…”
Section: A Medication Dispensingmentioning
confidence: 99%
“…This is particularly useful with complex patients who have multiple prescribers and more than one condition requiring treatment. Medication dispensing databases are increasingly available for pharmacists on large populations, particularly in countries that provide universal coverage for medicines [28][29][30].…”
Section: A Medication Dispensingmentioning
confidence: 99%
“…Currently among the 44 PSSAs that were assessed in two PSSA reviews, 7,8 only eight studies 6,9‐15 utilized a negative control index drug. One study identified a significant association between the negative control index drug and subsequent initiation of the marker drug, thus indicating bias.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to this research question, it could also be an indicator of inappropriate prescribing, that is, a prescribing cascade where an adverse event is treated with another drug rather than removing the cause for the adverse event. There has been an increasing number of publications using this methodology, with many more presented as conference abstracts that have yet to result in a published manuscript 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing number of publications using this methodology, with many more presented as conference abstracts that have yet to result in a published manuscript. [4][5][6] The PSSA uses a relatively simple design and computationally efficient approach. 5 Following a case-only design approach, the first step of the PSSA is to identify case-only patients who are those initiated on both an index and marker medication within a pre-specified exposure window (e.g., initiation of a marker drug within 365 days before or after index drug initiation).…”
Section: Introductionmentioning
confidence: 99%